Validation of reference evapotranspiration estimation methods for Palmeira das Missões, RS, Brazil (Research, Society and Development, 2021)
Water is a very important element for the development of agricultural crops, as it is part of their structures and means of nutrient transport. Meeting the water demand of the crop is fundamental for the dimensioning of the irrigation system and contributing to the sustainable use of water resources. Reference evapotranspiration (ETo) is one of the variables related to the amount of water that must be distributed per unit area. Their determination can be accomplished through different methods. This study aimed to evaluate ten daily ETo estimation models for the Palmeira region of Missões-RS. The performance of the methods was evaluated through a series of statistical indicators, in relation to the FAO Penman-Monteith (FAO-PM) method. The data were obtained from the automatic weather station of Palmeira das Missões, belonging to the National Institute of Meteorology (INMET) and comprise the period between 01/07/2008 until 09/01/2021, with 244 number of samples. The evaluations of the methods were performed using the total set of data. The methods were confronted through regression (bo), simple linear regression (R²), statistical indicators, such as the Pearson correlation coefficient (r), Camargo and Sentelhas index (c), Willmott index (d), absolute mean error (MAE) and the square root of the mean absolute error (RQME). For the micrometeorological conditions of Palmeira of the Missions-RS, the methods of Penman and Jesen-Haise were the ones that best estimated the ETo when compared to the FAO-PM standard.